Scientific parks in some countries and the possibility of benefiting from them in the Kingdom of Saudi Arabia - Al-Solami, Hanan Nour; Alsanee, Mona Muhammad (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify scientific parks in both the United States of America and the United Kingdom and the possibility of benefiting from in the Kingdom of Saudi Arabia. This is done by following the descriptive comparative approach to George Breda’s entry. In the light of the comparative analysis, the study reached several results, the most important of which were: All comparative countries stressed the importance of scientific parks in economic development and the role they play, and also all comparative countries agreed on the main motive of establishing scientific parks, which is the transition to a knowledge economy. In light of the results of the study, it recommended a number of proposed measures, including King Abdulaziz City for Science and Technology (KACST) should provide a space to attract companies to its headquarters, exchange experiences and benefit from companies in providing various job opportunities. Science parks in the Kingdom of Saudi Arabia should benefit from successful international experiences in this field, by identifying the best practices and international designs for scientific parks.